PROTOTIPE SISTEM PERINGATAN DINI BENCANA BANJIR PADA BASEMENT MEMANFAATKAN TEKNOLOGI E-MAIL - , FIRMAN DWIJAYA K. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Massive flooding caused by torrential rains can fill the basement with water very quickly, which contains the essential items that did not get moving. In this research the problem trying to be solved by detecting the level of water in the entry of water into basement. Then after the water into the basement and the water touches the sensor will be in the process of the microcontroller and then send an email to inform the flood and ebb automatically.